World War Two Iconoclasm: The Destruction and Reconstruction of memorials to Queen Victoria and Edward VII on the French Riviera - Gilles TEULIÉ (E-REA)
This essay explores the process linked to the desecration and subsequent rebuilding of monuments erected on the French Riviera to commemorate the British monarchs who had a positive influence on the development of Menton, Cannes and Nice as coastal resorts. When two statues of Queen Victoria and one of Edward VII were either defaced or completely destroyed during the Second World War, French agencies, to varying degrees, wanted to restore the statues to their rightful place. Although the examples used in this essay all had different operating modes, I argue that they nonetheless were motivated by similar factors which reveal a pattern to wartime iconoclasm and help explain its impact on postwar commemorative policy.